2020
DOI: 10.1111/apa.15473
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of problematic feeding in infants under 1 year of age undergoing frenotomy: A review article

Abstract: Ankyloglossia, commonly referred to as tongue tie, is a congenital anomaly where the tongue is abnormally tightly connected to the floor of the mouth, limiting its mobility. 1 This anomaly has been cited in literature dating back to the 1700s 2 and was routinely treated up through the 1940s, when infant formula use increased and breastfeeding rates declined. 3 Prevalence of tongue tie has been reported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…The most common symptoms were consistent with those described in previously published research. 7 For mothers reporting these symptoms, evaluation of a breastfeeding session to examine latch, position, and infant ability to sustain a breastfeeding session will assist providers in identifying differential diagnoses such as tongue-tie, or breastfeeding mechanics that can be adjusted to reduce maternal discomfort. With the significant decrease in maternal symptoms post-frenotomy without other intervention, tongue-tie should be considered as a potential cause of painful or difficult latching or infant chewing on the nipple during feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common symptoms were consistent with those described in previously published research. 7 For mothers reporting these symptoms, evaluation of a breastfeeding session to examine latch, position, and infant ability to sustain a breastfeeding session will assist providers in identifying differential diagnoses such as tongue-tie, or breastfeeding mechanics that can be adjusted to reduce maternal discomfort. With the significant decrease in maternal symptoms post-frenotomy without other intervention, tongue-tie should be considered as a potential cause of painful or difficult latching or infant chewing on the nipple during feeding.…”
Section: Discussionmentioning
confidence: 99%
“… 7 While researchers have explored maternal symptoms, such as nipple pain 8 - 13 more evidence is needed to examine the effects of frenotomy on the mother-infant dyad. 7 Current studies evaluating frenotomy for the treatment of tongue-tie lack the methodological rigor necessary to promote a change in screening, assessment, and treatment guidelines. 14 A recent study reported an 866% increase in frenotomy rates from 1997 to 2012.…”
mentioning
confidence: 99%
“…Durante a amamentação, essa restrição impede a pega efetiva na mama. Quando a pega é prejudicada, pode ocorrer dor no mamilo materno, diminuição da transferência de leite e dificuldades na alimentação do bebê (Hill & Pados, 2020).…”
Section: Anquiloglossia (Aql)unclassified
“…It is frequently associated with pain for the breastfeeding mother due to improper latch and increased friction of the tongue on the breast nipple. 2 Gastrointestinal (GI) distress can be the result of improper swallowing or excess ingestion of air (aerophagia). Although nonspecific, GI discomfort in infants can be distressing to parents.…”
Section: Introductionmentioning
confidence: 99%